(untitled) (Environment & Health, 2021)
Objective: We analysed the regulatory framework on the design of healthcare facilities built in the residential buildings, studied the conditions of their location and developed sanitary-and-antiepidemic requirements for them. Materials and methods: In the work, we used bibliosemantic (for the analysis of the use of legal regulation), theoretical (retrospective use of research data) and analytical methods. Results: According to the reform of the healthcare sector of Ukraine, at the primary level of medical care, the number of healthcare institutions is growing, in particular outpatient ones (outpatient clinics, family doctors’ offices, etc.), which are located in built-in (attached) non-residential premises of ground, first, and basement floors of multistory residential buildings. The authors of the article propose sanitary-and-hygienic and antiepidemic requirements for the location of built-in healthcare institutions at the hybrid type of the construction of residential and public part of the building, using parametric and target (object-by-object) methods. Conclusions: Taking into account that the outpatient healthcare institutions are the primary link in healthcare and make up the bulk of the entire healthcare institutions network, as well as the shortage of land for the construction of outpatient clinics in a separate building, the built-in healthcare institutions have become widespread and are located mainly in non-residential premises and residential buildings (ground, first, and basement floors), which is the element of hybrid construction. Developed sanitary-and-hygienic and antiepidemic measures for built-in healthcare institutionswill help to increase their epidemic safety, to prevent occupational diseases of medical staff.